2022
DOI: 10.3389/fnagi.2021.762649
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Netrin-1 in Mild Cognitive Impairment and Alzheimer’s Disease Patients

Abstract: Background and ObjectiveInflammatory mediators are closely associated with the pathogenesis of Alzheimer’s disease (AD) and mild cognitive impairment (MCI). Netrin-1 is an axon guidance protein and despite its capacity to function as a neuroimmune guidance signal, its role in AD or MCI is poorly understood. In addition, the association among netrin-1, cognitive impairment and serum inflammatory cytokines such as interleukin-17 (IL-17) and tumor necrosis (TNF-α) remains unclear. The aim of this study was to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 78 publications
0
6
0
Order By: Relevance
“…Glioblastoma is one of the most common tumors in neurosurgery, and evidence in recent years suggests that Netrin-1, as an atypical angiogenic ligand, may be involved in the promotion of neovascularization in glioblastoma [ 30 ]. Evidence that Netrin-1 is involved in the pathogenesis of Alzheimer's disease has been found in cells, animals, and clinical experiments, indicating that Netrin-1 may be involved in the regulation of neuroplasticity [ 31 33 ]. Studies on the regulation of Netrin-1 receptors in Parkinson's disease have also been reported [ 33 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glioblastoma is one of the most common tumors in neurosurgery, and evidence in recent years suggests that Netrin-1, as an atypical angiogenic ligand, may be involved in the promotion of neovascularization in glioblastoma [ 30 ]. Evidence that Netrin-1 is involved in the pathogenesis of Alzheimer's disease has been found in cells, animals, and clinical experiments, indicating that Netrin-1 may be involved in the regulation of neuroplasticity [ 31 33 ]. Studies on the regulation of Netrin-1 receptors in Parkinson's disease have also been reported [ 33 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence that Netrin-1 is involved in the pathogenesis of Alzheimer's disease has been found in cells, animals, and clinical experiments, indicating that Netrin-1 may be involved in the regulation of neuroplasticity [ 31 33 ]. Studies on the regulation of Netrin-1 receptors in Parkinson's disease have also been reported [ 33 35 ]. Another study pointed out that serum Netrin-1 concentration decreased after brain injury and could be used as a biomarker of traumatic brain injury [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent review article also shows that ncRNAs in exosomes can mediate nerve inflammation and promote the development of AD ( Weng et al, 2022 ). In addition, memory deficits are the main characteristics of AD, and improving memory deficits by regulating ncRNAs is also a future research direction ( Ju et al, 2021 ; Xiao et al, 2021 ; Zhang G. J. et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our data suggest that Neogenin receptors could play an important role during the metastatic spread of melanoma towards Netrin-1-expressing tissues such as the brain. Interestingly, studies have shown that Alzheimer’s disease, a neurodegenerative process characterized by accumulation of amyloid beta in brain tissue, which results in functional/cognitive decline, is associated with poor Netrin-1 expression [ 42 , 43 , 44 ]. This is not surprising given the contribution of Netrin-1 to synaptic function, which is involved in learning and memory [ 33 , 45 ].…”
Section: Discussionmentioning
confidence: 99%